Critical thinking and teacher’s profile: central competences in the educational process - Zedam, Samir (2021)
The concept of critical thinking was highlighted in most scientific classifications a couple of decades ago. Critical thinking is an essential skill that can simplify all aspects of human life. In its broad sense, it means the art of thinking about thinking. It is a reflective action and reasonable thinking that is focused on deciding what to believe or what to do. Today, our students are overwhelmed with information from all kinds of sources, in particular from various online platforms, and at the same time, critical thinking is the focal point missed in many students. Many scholars and educators believe in two approaches: on the one hand, is that a teacher’s profile plays the focal point and the pinnacle of the pyramid of the education process (teacher, student, and content), and on the other, critical thinking is the heart and the soul of learning. Our study aims to identify to what extent teachers should integrate critical thinking approach through tackling critical thinking in terms of the education process, its dimensions, and the importance of thinking critically for students who attend any education program. Moreover, this study explores the transfer of critical thinking skills from pre-service teacher training as an agent of change in the field of education into the classroom practice and achieving a student’s ability to think critically. As an intending result of this, the study is drawing general highlights of the significance of critical thinking, the role of a teacher in promoting and integrating critical thinking among students, and a set of strategies that can help teachers stimulate critical thinking during their lectures.